India - Karnataka : Financing Education in the Context of Economic Restructuring - World Bank (Washington, DC, 2013)
The study addresses four major concerns within the Bank's Economic Restructuring Program in Karnataka: 1) identifying the priority issues facing the education sector; 2) indicating possible areas for expenditure reform, to improve the efficiency, and equity of public spending in education; 3) identifying measures to strengthen the effectiveness of public expenditure; and, 4) assessing the resource requirements for school education. The report reviews achievements, and educational trends in the nineties, looking at the factors shaping Karnataka's education development, to then examine public expenditures on education, and the efficiency of public spending. Improvements in the effectiveness of public expenditures in education are proposed, namely in the input utilization of teachers, and non-teachers; in management strengthening of the private sector; and, decentralization in the education system. To attain the elementary, and secondary education goals, considerable financial allocations will be required, where the volume of additional requirements depends critically on the strategies adopted by the Government of Karnataka (GOK), particularly as these affect the expenditures on teachers. The analyses show that if the GOK adopts fiscally sustainable strategies in school education, provided fiscal reforms are successful, financing requirements for the educational system expansion of higher quality, could be met, mainly from its own resources, and private sector mobilization, as well as from the adoption of cost-reducing strategies to narrow the financing gap.